(untitled) (Società e diritti, 2024)
This essay, in which the author responds to commentaries and considerations , made by Giovanni Messina, Valeria Marzocco e Aldo Schiavello, on his book Complessità del diritto, interpretazione, ragione giuridica, intends to highlight the contribution that hermeneutic theory can provide to an adequate understanding of the complexity of contemporary law. Legal positivization works through the articulation of sources of several origins and authoritativeness, in an unstructured, fragmentary, fluid context with a network frame. In this scenario, pluralism represents an essential aspect of complexity. Interpretative